Crystal structure of ethyl 2-[(4-bromophenyl)amino]-3,4-dimethylpent-3-enoate - Zukerman-Schpector, Julio; Caracelli, I.; Stefani, Helio Alexandre; Khan, Amna N.; Tiekink, Edward R.T. (International Union of Crystallography, 2014)
In the title compound, C15H20BrNO2, there are two independent molecules (A and B) comprising the asymmetric unit and these adopt very similar conformations. In A, the dihedral angle between the CO2 and MeC=CMe2 groups is 80.7(3)°, and these make dihedral angles of 3.5(3) and 84.09(16)°, respectively, with the bromobenzene ring. The equivalent dihedral angles for molecule B are 78.4(3), 2.1(3) and 78.37(12)°, respectively. The most prominent interactions in the crystal packing are amine-N-H⋯O(carbonyl) hydrogen bonds between the two independent molecules, resulting in non-centrosymmetric ten-membered {⋯OC2NH}2 synthons. Statistical disorder is noted for each of the terminal methyl groups of the ethyl residues.